1998
DOI: 10.1136/gut.42.6.886
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis: the substantial human and financial costs

Abstract: A greater understanding of the natural history of acute pancreatitis combined with greatly improved radiological imaging has led to improvement in the hospital mortality from acute pancreatitis, from around 25–30% to 6–10% in the past 30 years. Moreover, it is now recognised that the first phase of severe acute phase pancreatitis is a systemic inflammatory response syndrome (SIRS), during which multiple organ failure and death often supervene. Survival into the second phase may be accompanied by local complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
147
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(158 citation statements)
references
References 66 publications
3
147
1
7
Order By: Relevance
“…The mean age of presentation in world literature was 6th decades. 11 The difference is probably explained due to alcohol being common in this part of world.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of presentation in world literature was 6th decades. 11 The difference is probably explained due to alcohol being common in this part of world.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators also concluded that the average overall hospital cost was $96,891. Fortunately, AP patients typically regain complete functional ability and can return to employment and other normal activities [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic infections occur at the first 4 weeks of the disease and reach to peak levels at 2 or 3 weeks. It has been reported that pancreatic infections are responsible for 80% of the deaths in AP (Neoptolemos et al, 1998;Quamruddin and Chadwick, 2000).…”
Section: Discussionmentioning
confidence: 99%